2006
DOI: 10.1523/jneurosci.3178-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cystine/Glutamate Exchange Modulates Glutathione Supply for Neuroprotection from Oxidative Stress and Cell Proliferation

Abstract: The cystine/glutamate exchanger (xCT) provides intracellular cyst(e)ine for production of glutathione, a major cellular antioxidant. Using xCT overexpression and underexpression, we present evidence that xCT-dependent glutathione production modulates both neuroprotection from oxidative stress and cell proliferation. In embryonic and adult rat brain, xCT protein was enriched at the CSF-brain barrier (i.e., meninges) and also expressed in the cortex, hippocampus, striatum, and cerebellum. To examine the neuropro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
254
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(279 citation statements)
references
References 64 publications
(95 reference statements)
14
254
2
Order By: Relevance
“…The finding that constitutive genetic deletion of GSTP1P2 did not alter accumbens levels of xCT, the catalytic subunit of system Xc- (Shih et al, 2006), is not supportive of a linkage between the previously reported cocaine-induced downregulation of system Xc- (Baker et al, 2003) and the changes produced in GSTP1P2 and cellular redox shown herein. Downregulation of xCT reduces extracellular glutamatergic tone on synaptic mGluRs and this is thought to contribute to the vulnerability to reinstate cocaineseeking (Kalivas, 2009).…”
Section: System Xc-and Cocaine-induced Changes In Redoxcontrasting
confidence: 97%
See 1 more Smart Citation
“…The finding that constitutive genetic deletion of GSTP1P2 did not alter accumbens levels of xCT, the catalytic subunit of system Xc- (Shih et al, 2006), is not supportive of a linkage between the previously reported cocaine-induced downregulation of system Xc- (Baker et al, 2003) and the changes produced in GSTP1P2 and cellular redox shown herein. Downregulation of xCT reduces extracellular glutamatergic tone on synaptic mGluRs and this is thought to contribute to the vulnerability to reinstate cocaineseeking (Kalivas, 2009).…”
Section: System Xc-and Cocaine-induced Changes In Redoxcontrasting
confidence: 97%
“…Samples were denatured, reduced in sample buffer, and loaded on a 10% Criterion XT Bis-Tris gel with MOPS running buffer (Bio-Rad). The proteins were transferred onto a PVDF membrane with an iBlot dry blotting system (Invitrogen, Carlsbad, CA), blocked in 5% milk in TBS-Tween, and incubated overnight at 4 1C in rabbit anti-GSH reductase (Abcam, 1 : 1000), rabbit antiglutaredoxin 1 (Abcam, 1 : 250), rabbit anti-GSTpi (MBL, 1 : 1000), rabbit anti-xCT (Shih et al, 2006;Szumlinski et al, 2004; 1 : 500), or rabbit anti-thioredoxin (Cell Signaling, 1 : 1000). After extensive washing in TBS-Tween (3 Â 10 min), the membranes were probed with goat antirabbit HRP-conjugated antibodies (Millipore, 1 : 10 000).…”
Section: Western Blottingmentioning
confidence: 99%
“…Although glioma cells appear to be highly dependent on system X c À -mediated cystine incorporation required for glutathione production and thus the scavenging of reactive oxygen species (Chung et al, 2005;Chung and Sontheimer, 2009;Pham et al, 2010), normal cells might be less vulnerable. This notion is supported by genetic deletion studies, that is, xCT-deficient mice are healthy in appearance and fertile (Sato et al, 2005;Shih et al, 2006;Liu et al, 2007). Moreover, resistance of tumor cells to a variety of anticancer drugs is often associated with increased glutathione levels (Huang et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Cystine, an oxidized form of two cysteines with a disulfide linkage, is utilized as a substrate for GSH synthesis in some types of brain cells (61). Cystine is taken up into the cell in exchange for glutamate via system xc-, which can be inhibited by a high extracellular glutamate concentration (62).…”
Section: Cystine Uptakementioning
confidence: 99%